Viruses, vaccines, and power : Russia's strategic use of information in the COVID-19 crisis - Tuominen, Ksenia (2024)
At the beginning of 2020, humanity faced a new global enemy: the coronavirus (COVID-19). While some countries viewed vaccine development solely as a means to improve public health, others saw it as an opportunity to advance their political agenda. One method used to accomplish these goals during the pandemic was by exercising sharp power, which involves intentionally disrupting the political and information environments of other countries. This thesis seeks to explore how Russia has used sharp power to advance its interests during the coronavirus pandemic.